Management of a Splenic Artery Aneurysm in the Third Trimester of Pregnancy - Oxana Zarudskaya; Madanika Subash; Anita Tamirisa; Nikolina Docheva; Balaji Reddy; Dani Zoorob (Case Reports in Obstetrics and Gynecology)
Background. Splenic artery aneurysm (SAA) is a rare but potentially fatal complication associated with high maternal and fetal mortality when occurring during pregnancy. Case. A 29-year-old G4P3003 at 34 4/7 weeks of gestation was admitted with left upper quadrant pain and newly diagnosed SAA in the hilum. She was scheduled for embolization of the SAA but the night before went into labor. A multidisciplinary team discussion was held, and the patient underwent successful primary low transverse c-section via Pfannenstiel skin incision followed by laparoscopic splenectomy under general anesthesia. She delivered a male newborn with birth weight of 2855 and Apgar score of 8/5. Summary and Conclusion. Early diagnosis and management of SAA are key for improved maternal and fetal outcomes. Our case demonstrates that through a multidisciplinary approach and anticipation of the possible clinical scenarios, good outcomes can be achieved.